Emotions, Masculinity and Sexualization in the Fieldwork. Researching Sex Markets in Argentina - Morcillo, Santiago (2019)
This paper presents a reflection on the role of gender relations, masculinities and forms of sexualization in social research. The current context of expansion of feminisms -particularly in Latin America and Argentina- amplifies the focus on the sexed and generated dimensions of research. Moreover, this conjuncture time highlights a set of tensions in power relations and affections in fieldwork. Taking into account these points, analysis is based on fieldwork from two investigations: one with women who offer commercial sex and other about men who pay for sex. I focus on sexual and gendered interpellations and the field of emotionality -understood as a space that connects meanings and bodies-, to essay a situated reading intersecting the methodological, epistemological and political perspectives.